The divine in the element of water. - Song, Jemima Ting Xi. (2011)
From one of the oldest beliefs systems in the world, Hinduism, came the root development of a visual culture. Its depiction of gods and goddesses, their divine powers and cosmic phenomena came in the form of mythologies that have prevailed over the centuries. This project of the stories of the gods, singles out the element of water as a recurring motif in Hindu myths, and peels off its symbolic layer to unveil spiritual truths.